Immune status of splenectomized patients following vaccination against encapsulated bacteria (Annals of Medical Research, 2021)
Aim: The current study aimed to observe the effectiveness of a pneumococcal vaccine and a Haemophilus influenzae vaccine in splenectomized patients by quantification of serum antibody and complement levels, analysis of T and B lymphocytes with flow-cytometry and determination of the percentage of Natural Killer cells and the CD4+ to the CD8+ lymphocyte ratio.Material and Methods: The study included 22 adult patients who had undergone splenectomy between May 1999 and December 2006. The Pneumo-23 vaccine was administered for protection against Streptococcus pneumonia to all patients, whereas the Act-HIB vaccine was administered for protection against Haemophilus influenzae type B to 12 patients after January 2002.Hemogram, IgG and IgM antibody concentrations, serum levels of Complement protein 3 and Complement Protein 4 were obtained and lymphocytes were analyzed whether they were CD3+ and CD19+ by flow cytometry. At the second time point, in 2009, CD4+/CD8+ T-cell ratio and the percentage of CD3/CD16+CD56 Natural Killer cells were evaluated in addition to aforementioned parameters.Results: All of the study patients had normal IgG levels. Three patients had low levels of IgM. C3 and C4 values were normal. Ten patients showed a low CD3+ T-cell distribution at 5 years. The percentage of CD19+ B-lymphocytes returned to normal. Sustained suppression of CD19 level was observed only in one patient with immune thrombocytopenic purpura. CD8 distribution was normal in all patients. At 5 years, reduced CD4 percentage was detected in 5 patients with immune thrombocytopenic purpura, 3 of whom had suppressed levels of Natural Killer cells concomitantly. Normal levels of IgG, C3, C4 and CD19+ B-cell percentages were found at the final laboratory assessment for all patients.Conclusion: Our findings indicate that immunological functions are restored following administration of the Pneumo-23 and Act-HIB vaccines. Further studies are needed to obtain a prognostic immune profile index that could help predict patients at high risk for post-splenectomy sepsis.
Keywords: Bacteria; splenectomy; vaccine